Blood Pressure and Vascular Calcification - Jensky, Nicole E.; Criqui, Michael H.; Wright, Michael C.; Wassel, Christina L.; Brody, Steven A.; Allison, Matthew A. (Hypertension (Dallas, Tex. 1979), 2010)
The aim of this study was to determine the associations between the presence and extent of calcified atherosclerosis in multiple vascular beds and systolic blood pressure, diastolic blood pressure, pulse pressure, mean arterial pressure, isolated systolic hypertension, and hypertension. A total of 9510 patients (42.5% women) underwent electron beam computed tomography scanning as part of a routine health maintenance screening. At the same visit, blood pressure was measured with the participant in the seated position using a mercury sphygmomanometer. Mean age was 58±11.4 years, and body mass index was 27.1±4.5. The prevalences of any calcification in the carotids, coronaries, subclavians, thoracic aorta, abdominal aorta, and iliacs were 31.9%, 57.2%, 31.7%, 37.0%, 54.3%, and 48.8%, respectively. In separate multivariable logistic models containing traditional cardiovascular disease risk factors, pulse pressure and systolic blood pressure were significantly associated with the presence of calcification in all of the vascular beds except the iliacs and subclavians, respectively, with pulse pressure having stronger magnitudes of the associations for most of the vascular beds. Age-stratified analyses indicated that these associations were stronger in those >60 years of age compared with subjects <60 years of age, and sex-stratified analyses demonstrated that men had a greater association compared with women. Also, the magnitudes of the associations for isolated systolic hypertension were, in general, larger than those for hypertension. Pulse pressure and isolated systolic hypertension are robust and important correlates for calcified atherosclerosis in different vascular beds. Isolated systolic hypertension may be clinically relevant in diagnosing or preventing calcified atherosclerosis.